TRANSLATION ANALYSIS OF THE NEWS SCRIPT ON REPORTING GEORGE FLOYD DEATH IN THE UNITED STATES - Mohammad Naufal Ardiansyah; Sri Endah Tabiati; Esti Junining (Journey: Journal of English Language and Pedagogy, 2023)
This article aims examines the translation accuracy and find out some translation techniques on a news script of George Floyd case report in several media. This article uses descriptive qualitative method to analyze translation errors of on the news script and involves the researcher as the primary instrument to gain the data taken from the official website of BBC, CNN Indonesia and TIMES Indonesia and twitter. The data were analyzed in order to investigate and recommend the reporters and readers to understand comprehensively about transferring messages especially on sensitive issue George Floyd Death in the United States considered as a taboo case. Showing by these cases, the translation conducted a different and omission meaning. The result of this article figures out some translation errors those are different meaning or wrong meaning, and omission which tend to cause misperception from the readers. Since, the process of translation in the media definitely affects readers' understanding on how the news reports and it can influence people's actions and assumptions.